DIGITAL PICTORIAL LEARNING MEDIA FOR TEACHING AFFIXES OF SEVENTH GRADE OF JUNIOR HIGH SCHOOL - Laila Nuzulia Rahma; Supriyono; Nita Sutanti (Universitas Islam Balitar, 2021)
Perception shows that there was an issue in mastering lexicon and the nonappearance of learning media. The point of this inquire about is creating directions media for dominance of attaches lexicon within the graphic content through the utilize of Computerized Pictorial of Fastens Amusement (POAME) media. This inquire about is inquire about and improvement (R&D). The inquire about subjects were 7th-grade students’ junior tall school. The usage was within the indeed semester of the 2019/2020 scholastic year. The analyst did perception in three schools with the comes about of the meet and perception appeared that the understudies had not however caught on the joins lexicon and there were no media for learning, whereas the records appeared that the students' scores were underneath least completeness criteria, which was a normal of 50, 70.7, 77,3, Amid media advancement, the media is inspected by material experts and media specialists so that discernments may be tried and get result 91.4% from instructor reactions and 89.6% student responses. This was proved that the POAME media is valid and feasible to use as an alternative media for learning affixes vocabulary for 7th grade of MTs Darussalam Kademangan. This is evident from the teachers’ and students’ responses who fall into the very feasible category with an interval of 81% - 100%.